PERAN BADAN PERTANAHAN NASIONAL DALAM PENYELESAIAN SENGKETA PERTANAHAN MELALUI MEKANISME MEDIASI - Yudha Wismaya, Made; Novy Purwanto, I Wayan (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 05, Juli 2014)
Indonesia is one country agricultural country, so that the soil has a veryimportant meaning to the lives of the people of Indonesia . Once the importance of theposition of the ground for man not infrequently lead to disputes about land.Theoretically dispute resolution can be done through two ways, namely through theformal justice mechanisms in court (Litigation) and outside the judicial process (Non-Litigation). One form of settlement out of court is mediation. Mediation is a disputeresolution through negotiation with the help of a neutral third party (mediator) for thecompletion of forms that can be agreed upon by the parties. This study aims tounderstand and know about What is the Role of the National Land Agency inresolving land disputes through mediation mechanism. In this study, using descriptivenormative method. Settlement of land disputes can be resolved through mediationmechanism by BPN (National Land Agency). As a mediator, BPN has the role ofhelping the parties understand each other's views and help look for things that areimportant to them. Mediators facilitate the exchange of information , encouragediscussion about the differences of interests, perception, interpretation of situationsand problems and regulate expression of emotion.
Keywords: Role, Land Body, Mediation